2020
DOI: 10.24085/jsaa.v8i1.4184
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Student Biographical Questionnaire (BQ) Online Platform for Effective Student Success

Abstract: Knowing relevant information about students entering the higher education (HE) system is becoming increasingly important, thus enabling higher education institutions (HEIs) to design effective studentcentred support programmes. Therefore, HEIs should ascertain all relevant information about their students before the commencement of the academic year. Doing so means that institutions have a head start in understanding the types of support that will be required for different students throughout the year. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The current research targeted the entire cohort of 2019 first-time, first-year undergraduate students (n = 5,912). The inclusion criteria to participate in this research, which was used to extract the sample, was as follows: being 18 years of age or older; being a first-time, first-year undergraduate student; studying full-time; completion of the Biographic Questionnaire [16], which is a baseline survey at intake; pursuing either a professional bachelor's degree (a programme that is generally four years or longer) or a general bachelor's degree (generally a threeyear programme); and being assigned progress codes at the end of the 2019 academic year. All students provided informed consent prior to participating in the study.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The current research targeted the entire cohort of 2019 first-time, first-year undergraduate students (n = 5,912). The inclusion criteria to participate in this research, which was used to extract the sample, was as follows: being 18 years of age or older; being a first-time, first-year undergraduate student; studying full-time; completion of the Biographic Questionnaire [16], which is a baseline survey at intake; pursuing either a professional bachelor's degree (a programme that is generally four years or longer) or a general bachelor's degree (generally a threeyear programme); and being assigned progress codes at the end of the 2019 academic year. All students provided informed consent prior to participating in the study.…”
Section: Samplementioning
confidence: 99%
“…Several studies have explored factors and determinants of throughput and student success [13][14][15][16]. These studies found that the determinants of student success are complex, identifying high school academic achievement [13,17], family background [15] and the students' ability to integrate into the different aspects of university life, including social communities and teaching and learning [14] as key determinants of academic success.…”
Section: Introductionmentioning
confidence: 99%